PROFESSIONAL COMPETENCE MASTERS OF INDUSTRIAL TRAINING OF PROFESSIONAL (VOCATION-TECHNICAL) EDUCATION INSTITUTIONS IN THE AUTOMOBILE INDUSTRY (Innovative professional education, 2024)
The article analyzes the need for professional competence of masters of industrial training of vocational (vocational and technical) education institutions in the process of professional training for their successful professional activity in modern conditions of the organization of the educational process.
Keywords: master of industrial training, competence approach, professional competence, structure of methodical competence